INOVASI PELAYANAN ADMINISTRASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PINRANG - Irma, Irma; Malik, Ihyani; Pratama, Muhammad Randy (Universitas Muhammadiyah Makassar, 2024)
This research aims to analyze public service innovation through UP3SK at the Pinrang Regency Population and Civil Registration Service. This research is qualitative research, the research carried out is descriptive. The results of the research show that public service innovation through UP3SK at the Pinrang Regency Population and Civil Registration Service can be seen based on innovation attributes according to Rogers. In the